COMING OF AGE: AN ANALYSIS OF A YOUNG ADULT CHARACTER DEVELOPMENT IN ELLEN HOPKINS' YOUNG ADULT NOVEL CRANK - Fajarrani, Rizky (2013)
Penelitian yang berjudul Coming of Age: An Analysis of a Young Adult Character Development in Ellen Hopkins' Young Adult Novel Crank adalah analisis tekstual novel remaja berjudul Crank karya Ellen Hopkins yang memfokuskan kepada isu coming of age di dalam novel. Pembahasan terpusat pada karakter wanita utama untuk mengungkap bagaimana isu coming of age ditunjukkan didalam novel. Pembahasan dalam penelitian ini didukung oleh teori perkembangan dan karakteristik remaja, (Bucher and Hinton, 2010), coming of age (e.g. Millard, 2007 and Fox, 2010) dan identitas (Barker, 2002). Penelitian ini menggunakan metode kualitatif tepatnya analisis tekstual. Hasil penelitian menunjukkan bahwa coming of age menggambarkan peningkatan perubahan yang dialami oleh karakter utama, Georgia, dari anak perempuan yang memiliki pola pikir sederhana menjadi anak perempuan yang lebih dewasa dengan pola pikir yang lebih tinggi. Dengan kata lain, isu coming of age menunjukkan proses pendewasaan seorang remaja. Abstract The present research entitled Coming of Age: An Analysis of a Young Adult Character Development in Ellen Hopkins' Young Adult Novel Crank is a textual analysis of Ellen Hopkins' young adult fiction focusing on the issue of coming of age in the novel. The discussion focuses on the main female character in the story to reveal the ways coming of age issue is addressed in the novel. Therefore, the discussion is framed within the theories of the characteristic and development of young adult (Bucher and Hinton, 2010), coming of age (e.g. Millard, 2007 and Fox, 2010) and identity (Barker, 2002). The research utilizes a qualitative method particularly textual analysis. The result of the present research shows that coming of age describes a progress shift which is experienced by the main character, Georgia, from a teenage girl who is simple-minded to a mature adult with higher-level of thinking. In other words, coming of age issue shows the process of adolescents from immaturity to maturity.